2019
DOI: 10.18699/vj19.519
|View full text |Cite
|
Sign up to set email alerts
|

Conjugacy of two types of phenotypic variability of small-leaved linden

Abstract: The properties of five bilaterally symmetrical features of the leaf blades of the small-leaved linden (Tilia cordata Mill.) in four populations of the Moscow Region in 2014–2017 were studied. The angle trait was excluded, because it possessed the property of directional asymmetry. Instead, a new linear trait was used: the distance between the base of the second vein of the first order and the base of the first vein of the second order on the first vein of the first order. The population difference in fluctuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…Both developmental stability and canalization emerge as by-products of regulatory complexity and redundancy in developmental systems and share overlapping developmental bases (Siegal & Bergman 2002). We also found FA was more likely to have positive correlations with RDPIs in all the three experiments, consistent with others (Baranov et al 2019;Gómez-Robles et al 2013;Leung et al 2017;Tonsor et al 2013). Although LF-CV or IN-CV had more negative correlations with both FA and RDPI s in EXP I, but IN-CV had more positive ones with them in EXP II.…”
Section: Correlations Among Variablessupporting
confidence: 84%
See 1 more Smart Citation
“…Both developmental stability and canalization emerge as by-products of regulatory complexity and redundancy in developmental systems and share overlapping developmental bases (Siegal & Bergman 2002). We also found FA was more likely to have positive correlations with RDPIs in all the three experiments, consistent with others (Baranov et al 2019;Gómez-Robles et al 2013;Leung et al 2017;Tonsor et al 2013). Although LF-CV or IN-CV had more negative correlations with both FA and RDPI s in EXP I, but IN-CV had more positive ones with them in EXP II.…”
Section: Correlations Among Variablessupporting
confidence: 84%
“…More positive than negative correlations among FA, CV and RDPI s with higher densities and infertile soil suggested environmental stresses might have uncovered the cryptic variations at both phenotypic and genetic levels (Nijhout & Reed 2014;Snell-Rood et al 2015), leading to higher FA, greater phenotypic variations and stronger ability to avoid passive phenotypic responses to environmental stresses. And environmental factors may play a coordinated role in promoting the cooperation between plasticity, canalization and stability (Baranov et al 2019), which should be bene cial for dealing with stresses. Elgart et al (2015) showed how stress mediates tuning of developmental robustness and plasticity: when the stress is mild enough, plastic changes in some processes may prevent drastic changes in more robust traits; when the stress is su ciently severe, this buffering may no longer be able to prevent such overt changes, leading to phenotypic variability subjected to selection that might assist survival at the population level.…”
Section: Correlations Among Variablesmentioning
confidence: 99%
“…Genetic assimilation is the subsequent genetic fixing of the new trait in the population. Some recent experimental and theoretical works have established a quantitative basis for these classic concepts of Waddington [36].…”
Section: Epigenetics As a New Branch Of Genetics 31 Interspecific DImentioning
confidence: 99%
“…Plastic variability (PI) of the size of morphological characters is often associated with asymmetry. If there is such a correlation, then the increase in FA is explained by an increase in the size of characters, but not by deviation in developmental stability [19].…”
Section: Introductionmentioning
confidence: 99%